Students’ Well-Being Since the Pandemic: An Ongoing Concern - Papi, Cathia (Journal of Contemporary Issues in Education, 2025)
Management of the health crisis reduced social contact for children and adolescents and led them to spend months schooling from home. During case studies conducted in 12 schools in 2021 and 2022, interviews with principals and school board directors revealed an increase in student difficulties whose dimensions vary widely. To assess the extent to which the difficulties identified were present throughout Quebec in 2023, an online survey about students was sent to all school boards. A total of 309 elementary and high school principals responded to the survey. It appears that difficulties have increased since the pandemic. Those difficulties have various dimensions; they are not only cognitive and methodological, but also and especially social, affective and psychological. Although they do not affect all students and tend to diminish over time, the aftereffects of the health crisis are still apparently present and students continue to require help overcoming difficulties they have encountered.